Pembelajaran Lintas Budaya: Penggunaan Subak sebagai Model “Ecopedagogy” - Surata, Sang Putu Kaler (Jurnal Kajian Bali (Journal of Bali Studies); Vol 3 No 2 (2013): PARIWISATA BALI DAN WARISAN BUDAYA, 2013)
Abstract Ecopedagogy is a form of cross-culture learning thatintegrating the socio-ecology principles, cultural literacyand techno-literacy. This paper describes a participatoryaction research (PAR) with utilize the Bali’s traditionalrice farmers organization or subak as place-based learning.Since August 2012 to July 2013, 40 student teachers fromUniversity of Mahasaraswati Denpasar involved in series ofPAR cycles. At the first PAR cycle, students visited ricefieldsand schools to observe and interview farmers, teachers andschool students. They found that the knowledges, attitudesand practices toward sustainable learning of farming systemfrom farmers, teachers, student teachers and students havedecreased significantly. Thus students design learningmaterial by using subak as source of topics, concepts, placesor examples. Its included interactive learning strategies(such as photo-voice and participatory video), learningmodules and a student’s textbook. The learning materialwas implemented, tested and evaluated through series ofaction research in collaboration with school students andteachers. Finally students wrote thesis and scientific paper as other learning outcomes. This PAR showed a simplemodel of community service and research-based learning,in which provide chance for students to enhance theirbasic learning competencies: ability for implementing oftheir concern, attitudes, skills and understanding of certaintopics or problems.
Keywords: cross-culture learning, subak, ecopedagogy, socio-ecology, character education